2015
DOI: 10.1596/1813-9450-7422
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneous Effect of Information on Student Performance: Evidence from a Randomized Control Trial in Mexico

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 4 publications
1
25
0
Order By: Relevance
“…This is linked to the fact that females are more likely to be enrolled in college. Avitabile et al (2015) demonstrate that females are more likely to increase their schooling effort after being exposed to information related to education and future career prospects.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This is linked to the fact that females are more likely to be enrolled in college. Avitabile et al (2015) demonstrate that females are more likely to increase their schooling effort after being exposed to information related to education and future career prospects.…”
mentioning
confidence: 91%
“…Based on this evidence, several information-based policy experiments have been conducted around the world. Information on labour market wages around the world has been used in China (Loyalka et al, 2013), Colombia (Bonilla et al, 2015), Finland (Pekkala et al, 2015), India (Sequeira et al, 2016), Mexico (Avitabile et al, 2015) and the United States of America (Fryer, 2013). Others have focused instead on knowledge about costs and financial constraints; for example, Hoxby and Turner (2013) in the United States of America, and McGuigan et al (2015) in England.…”
Section: Introductionmentioning
confidence: 99%
“…5 The use of ENLACE in the CM program possibly increased teacher effort, but as SEP required the use of external proctors, it is unlikely that teachers were able to directly manipulate student responses. Previous work (Avitabile andde Hoyos, 2018, De Hoyos et al, 2018) has shown that ENLACE tests in primary education are correlated with later learning and labor market outcomes.…”
Section: Enlace Testsmentioning
confidence: 98%
“…The switch in the sign of the gender coefficient is explained by the girls' lower performance in mathematics in Grade 12. See results in online Appendix 5 and Avitabile and De Hoyos (2015) for a discussion on this issue.…”
Section: Econometric Modelmentioning
confidence: 99%